O uso de estratégias na aprendizagem dos tempos verbais - Duarte, Yara (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The purpose of the study reported on in this paper was to investigate the strategies used by Brazilian university students in tasks commonly found in E.F.L. classrooms involving the use of verb tenses. The elicitation format required students to write essays and to fill in the blanks in the exercises using the apropriate verb tenses. The subjects were then asked in individual interviews to justify their choise of verb tense, i. e., to retrospectively self-observe (Cohen & Hosenfeld, 1981). Data analysis consisted of a qualitative analysis of transcriptions of self-report plus linguistic data. Through analysis of the content of students reponses, it was possible to identify the basic strategies that students responses, it was possible to identifu the basic strategies. Althrough the value of mentalistic approaches to research has been questioned, I believe that they were important to determine learner’s choice of verb tenses and the reasoning behing the form they used, thus shedding light on the process of foreign language learning.